Information technology: law and practice law and emerging technology cyber law and e-Commerce - "Sharma, Vakul" (New Delhi, 2013)
This book is not an Internet download as most books of this genre are. It is an original work. It is more than a mere section-wise commentary of the Information Technology Act, 2000. Numerous illustrations, concept notes and examples make the subject interesting and comprehensible. It is an original text as it attempts to interpret the true legislative intent behind the Act by referring to and applying the Supreme Court judgments for better assimilation and understanding of its various provisions. The author has tried to assimilate the thoughts of Judges, Lawyers, Civil Servants, Police Officers, Technocrats and Students whom he met during his public lectures, discussions, workshops, seminars across the length and breadth of the country over the past many years. It is for the first time that a critical appraisal of powers and functions of the Cyber Regulatory Appellate Tribunal, Controller of Certifying Authorities, Adjudicating Officers and Police Officers under the Information Technology Act has been attempted. It is a useful book for the Legislators, Judges, Adjudicating Officers, Lawyers, E-commerce portals, IT professionals, Software developers, Certifying Authorities, Auditors, Network service providers, Call centers, Bankers, Depository participants, Stock investors, Online-publishers, Journalists, Satellite/TV channels, Multimedia houses, Entertainment companies, IPR Cells of Chambers of Commerce; Cable operators, Law enforcement and Security Agencies, Government bodies, Law, Management and Information Technology students. It would also help the Government bodies/institutions and the corporate sector to conduct due-diligence analysis before adopting a Digital Signature regime and e-Governance practices. One of the most analytical and original law books to come out in years. You just cannot ignore this book!
Keywords: "Information technology- law, Cyber law"